PENGARUH KOMPRES KAYU MANIS TERHADAP PENURUNAN NYERI PADA PASIEN ARTHITIS GOUT DI DESA MEKAR JAYA - Harahap, Ardika Tri Nanda; Selvy Afrioza; H. A. Y. G. Wibisono (Nusantara Hasana Journal, 2022)
High uric acid levels cause joint and bone pain, these complaints were experienced by 60 people identified with gouty arthritis in Mekarjaya Village. If not treated immediately, gouty arthritis can lead to joint deformity and sleep disturbances. To deal with this disease, researchers focus on alternative medicine using safe and inexpensive plants, namely cinnamon compresses. Another benefit of cinnamon as an anti-rheumatic, pain reliever and appetite enhancer. Providing an alternative treatment solution for cinnamon compresses for reducing pain scale in gouty arthritis patients in Mekar Jaya Village. Pre-experimental research with one group pretest research design, cinnamon compress intervention, posttest. The research subjects amounted to 30 respondents according to the inclusion and exclusion criteria, then data analysis was carried out with the sign test. The cinnamon compress intervention had an effect on reducing the pain scale, where before the intervention was given an average of 2.07 after the intervention was 1.17, meaning there was a decrease of 0.9. Based on the results of the sign test, the P value was 0.000 (P <0.05), so that there was an effect of cinnamon compress on reducing pain scale. Giving cinnamon compresses effectively reduces pain scale in gouty arthritis patients in Mekar Jaya Village.